PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP KEINGINAN BERPINDAH KERJA PADA KARYAWAN HOTEL AMAROOSSA GRANDE BEKASI - Jeni Hari Agustianah; Aris Budiono (LPPM Universitas Asa Indonesia, 2016)
Purpose- The purpose of this research is to find out the impact of employee’s satisfaction, and organization commitment on staff turnover individually, and simulatenously at Amaroosa Hotel in Bekasi. Design/methology/approach- The simple random sampling technique was implied and analyzed by SPSS bersion 20. The total of respondentas are 74 person. The multiple regression is selected as the suitable method to conduct the serial tests. Findings- The motivation of staff turn over are based on organization commitment and the staff also influenced by a better offer from the competitor as the high demand is happening. Research limitations-The single object and the limited respondents of this research is a limitation of this study. Practical implications- The evaluation of the market price, and employee’s satisfaction should be measure gradually, and periodically